MARKETING STRATEGY IN SMALL BUSINESS ENTERPRISES - PAVLISHYNA, NINA; RIEZANTSEVA, VALERIIA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article analyzes the features of marketing activities of enterprises related to small business Defines the criteria by which enterprises are classified in one way or another. It is noted that the use of only quantitative characteristics, such as the number of staff or turnover indicators can not fully characterize the peculiarities of small businesses. After all, a small enterprise is a specific subject of market relations, which has fundamentally new qualitative characteristics, namely: the union in one person owner and entrepreneur (and often half of the functions), focus on innovation, simplified communication and information systems, work in conditions of fierce competition. The characteristic features inherent in the marketing strategy of an enterprise of any size are identified and specific features inherent exclusively in small businesses are given. Based on the selected features, marketing strategies that can be used by small businesses are summarized. Having a well-thought-out formalized marketing strategy, its adaptation to the conditions of the enterprise, allows to use such strategic advantages of a small enterprise as flexibility, maneuverability, adaptability and reduce the dependence on big business and competition in the market. A number of obstacles that hinder the full implementation of marketing strategy in the activities of small businesses are outlined. In particular, the most important of them are: intuition of marketing activities, lack of consistency between marketing strategy and other strategies in the enterprise, the lack of a separate specialist who would deal professionally with marketing issues and interaction with the target segment. Prospects for further research in this area are outlined, taking into account the requirements of the virtual environment and the focus of the market economy on digitalization.
Keywords: marketing activities; marketing strategy; small business; entrepreneur